FREQUENCY OF HEPATITIC C VIRURS (HCV) GENOTYPES AND SUBTYPES - Farukh Imtiaz; Shehzad Tarique; Safder Pervez; Saba Faiz; Zahid Hussain; Sarmad Saeed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Viral hepatitis is still a major global public health concern; HCV is especially worrisome because it can develop chronic hepatitis that lasts a long time in vulnerable people. HCV is an encapsulated virus that was first discovered in 1989. It presents major clinical concerns as the second most common cause of viral hepatitis worldwide. Determining the HCV genotype is essential because treatment duration has been observed to differ according to genotype. While some genotypes react to treatment more quickly, others take longer to successfully eradicate the virus and achieve sustained virologic response (SVR). HCV infection is a major global health concern, because it is generally asymptomatic until clinical signs appear, it can be difficult to correctly estimate its incidence rate.Objective: To assess the frequency of HCV genotypes and subtypes in people who are infected with hepatitis C Virus.Study design: a cross sectional studyPlace and Duration: This study was conducted at   Khairpur Medical college teaching Hospital, Khairpur Mir's, Sindh, Pakistan  from September 2022 to September 2023Methodology: Participants in the study had to be 16 years of age or older and chronically infected with HCV. All the participants were positive for HCV RNA. These patients had 600 blood samples taken in order to ascertain their HCV genotypes. As directed by the Abbott Real Time HCV Genotype assay kit, RT-PCR was used for the genotyping analysis. Using fluorescent-labeled probes specific to each genotype, this kit detects the six major HCV genotypes (1-6) and their subtypes (1a and 1b). Primers target the 5'UTR region for genotypes 1-6 classification and the NS5B region for subtype detection of 1a and 1b.Results: There were a total of 600 HCV positive samples assessed in this study subjected to genotyping. Out of 600 samples, 348 (58%) were males and 252 (42%) were females. This shows that the number of females in this research was lesser than males. The most frequent genotype was HCV genotype 3 affecting 85% of the total patients.Conclusion: There were found to be eight genotypes and subtypes of hepatitis C virus, with genotype 3 being the most common.